Fos immunocytochemical studies on the neuroanatomical sites of action of acute tyrosine depletion in the rat brain. - Le Masurier, M; Cowen, P; Sharp, T (2004)
RATIONALE: Acute depletion of brain tyrosine using a tyrosine-free amino acid mixture offers a nutritional approach to reduce central catecholamine function. Recent preclinical data suggest that tyrosine-free amino acid mixtures may have region-specific effects through targeting dopamine neurones. OBJECTIVES: Here we used fos immunocytochemistry to examine the neuroanatomical sites of action of a tyrosine-free amino acid mixture administered either alone or combined with amphetamine. METHODS: Rats (male, Sprague Dawley, 240-260 g) were administered (IP) either a tyrosine-free amino acid mixture (1 g/kg), or the same mixture supplemented with tyrosine and phenylalanine (1 g/kg). Mixtures were injected twice (1 h apart) followed 1 h later by amphetamine (2 mg/kg SC). Two hours later, cardiac perfusion was performed and brains were processed for fos immunocytochemistry. Fos positive cells were counted using computer imaging software. RESULTS: The tyrosine-free amino acid mixture alone did not alter fos expression in ten regions of the rat forebrain compared to saline controls. However, the mixture reduced the increase in fos expression evoked by amphetamine. This effect was region-specific and was greatest in caudate putamen, nucleus accumbens, bed nucleus stria terminalis and lateral habenula, and lacking in other areas including cingulate and insular cortices, lateral septum and central amygdaloid nucleus. Moreover, in most regions the effect of the tyrosine-free mixture was less after tyrosine and phenylalanine supplementation. CONCLUSIONS: In summary, a tyrosine-free amino acid mixture reduced amphetamine-induced fos expression but this effect was region-specific and included dopamine-rich regions. These data further support the idea that tyrosine depletion strategies have potential as treatments for mania and other hyperdopaminergic states.